Adaptasi Mahasiswa KKN Kebangsaan dalam Menghadapi Culture Shock di Negeri Latu, Kecamatan Amalatu, Kabupaten Seram Bagian Barat - Fahrul Ramadhan Afnil; Abdul M Ukratalo; Eko Saputra N Basyarewan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The National Community Service Program (KKN) is an initiative in higher education aimed at enhancing student engagement in community service. In this program, students are expected not only to apply the knowledge they have learned but also to interact with local communities that have different cultural backgrounds. This study aims to understand the adaptation process of KKN students facing culture shock in Negeri Latu, Amalatu District. This research is analytical in nature, utilizing primary data with a cross-sectional approach. The sample consists of 12 KKN students in Negeri Latu, who were provided with a Google Form link containing a questionnaire to fill out. The obtained data were then analyzed using univariate and bivariate analyses. The results indicate that the majority of students have a high level of adaptation, with 63.6% of respondents categorized as high and 36.4% as moderate. Conversely, the majority of respondents experienced low levels of culture shock, with 90.91% in the low category and only 9.09% in the moderate category. Chi-square test analysis reveals a significant relationship between the adaptation process and culture shock. This means that students who are able to adapt well tend to experience lower levels of culture shock.